2021
DOI: 10.12688/wellcomeopenres.16560.1
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference in Latin America and the Caribbean: A systematic review and meta-analysis

Abstract: Background: High neck circumference (NC) is associated with high burden diseases in Latin American and the Caribbean (LAC). NC complements established anthropometric measurements for early identification of cardio-metabolic and other illnesses. However, evidence about NC has not been systematically studied in LAC. We aimed to estimate the mean NC and the prevalence of high NC in LAC. Methods: We conducted a systematic review in MEDLINE, Embase, Global Health and LILACS. Search results were screened and studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
0
2
1
1
Order By: Relevance
“…Application of the ESS showed no change after treatment, unlike other studies 15 , 18 , 23 that observed improvement in sleepiness. However, the present results agree with those reported by Ieto et al (2015) 13 and Kayamori (2015) 15 who also found no improvement in sleepiness after MT.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Application of the ESS showed no change after treatment, unlike other studies 15 , 18 , 23 that observed improvement in sleepiness. However, the present results agree with those reported by Ieto et al (2015) 13 and Kayamori (2015) 15 who also found no improvement in sleepiness after MT.…”
Section: Discussioncontrasting
confidence: 82%
“…We believe that the fact that the study took place during the SARS-CoV-2 pandemic may be linked to weight gain, as reported in some studies [20][21][22] . Espinoza-López et al (2021) 23 suggested neck circumference as an anthropometric indicator since it is intimately related to different diseases, including obesity. Therefore, the correlation found between neck circumference and the energy/ fatigue and emotional well-being health components of the SF-36 demonstrates that neck circumference is not only a physical measure but may also be an indicator of important health issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the assessed studies used different operative definitions of NC, the meta-analysis could not determine the prevalence of patients with large NCs. 12 This finding stresses the need to define an optimal NC cut-off point for the Colombian population.…”
Section: Discussionmentioning
confidence: 98%
“…En la salud pública, los indicadores antropométricos cumplen un papel importante, ya que son criterios de diagnóstico o factores de riesgo para algunas enfermedades no transmisibles (9). El IMC es el indicador antropométrico más utilizado para el diagnóstico de sobrepeso y obesidad (2), pero a pesar de su gran popularidad se conoce que tiene un valor predictivo muy limitado, puesto que no diferencia con precisión los componentes del peso corporal y tampoco la distribución de la misma (10).…”
unclassified